2016
DOI: 10.3390/ijms17060904
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and Therapeutic Strategies against Parkinson’s Disease: Recent Perspectives

Abstract: Parkinsonism is a progressive motor disease that affects 1.5 million Americans and is the second most common neurodegenerative disease after Alzheimer’s. Typical neuropathological features of Parkinson’s disease (PD) include degeneration of dopaminergic neurons located in the pars compacta of the substantia nigra that project to the striatum (nigro-striatal pathway) and depositions of cytoplasmic fibrillary inclusions (Lewy bodies) which contain ubiquitin and α-synuclein. The cardinal motor signs of PD are tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
87
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(95 citation statements)
references
References 294 publications
(344 reference statements)
2
87
0
1
Order By: Relevance
“…have PD, and about 60,000 Americans are newly diagnosed each year [1,2]. Fifty percent more men are affected than women [3].…”
Section: Introductionmentioning
confidence: 99%
“…have PD, and about 60,000 Americans are newly diagnosed each year [1,2]. Fifty percent more men are affected than women [3].…”
Section: Introductionmentioning
confidence: 99%
“…Their etiologies remain uncertain, though there are a number of established pathogenic factors, including oxidative stress, neural apoptosis, mitochondrial dysfunction, excitotoxicity, impairment of the ubiquitin-proteasome system and inflammation (2,3). Neuroprotective therapy has been suggested to prevent disease progression by inhibiting the action of pathogenic factors, for instance, by reducing the production of reactive oxygen species (ROS) (4). Overproduction of ROS may cause oxidative damage to biomolecules and subsequently DNA damage, ultimately leading to the development of neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors play a role in chronic neurodegeneration which leads to Parkinson's disease (PD), including inflammation [1], cytokine syntheses and release [1], protein recycling-ubiquitination problems [2], glial cell activation [3], loss of astrocyte support [4], neurotrophic factors [2], nitric oxide synthase [5] and mitochondrial dysfunction [2]. However, recent reports have shown that circulating cells [6] are also involved in disease progression, which coupled with vascular damage [7], points to both peripheral and innate factors and cell involvement in the ensuing demise of neurons.…”
Section: Introductionmentioning
confidence: 99%